The axolotl genome and the evolution of key tissue formation regulators - Nowoshilow, Sergej; Schloißnig, Siegfried; Pippel, Martin; Powell, Sean (Nature, 2018)
Salamanders serve as important tetrapod models for developmental, regeneration and evolutionary studies. An extensive molecular toolkit makes the Mexican axolotl (Ambystoma mexicanum) a key representative salamander for molecular investigations. Here we report the sequencing and assembly of the 32-gigabase-pair axolotl genome using an approach that combined long-read sequencing, optical mapping and development of a new genome assembler (MARVEL). We observed a size expansion of introns and intergenic regions, largely attributable to multiplication of long terminal repeat retroelements. We provide evidence that intron size in developmental genes is under constraint and that species-restricted genes may contribute to limb regeneration. The axolotl genome assembly does not contain the essential developmental gene Pax3. However, mutation of the axolotl Pax3 paralogue Pax7 resulted in an axolotl phenotype that was similar to those seen in Pax3−/− and Pax7−/− mutant mice. The axolotl genome provides a rich biological resource for developmental and evolutionary studies.